1993
DOI: 10.1289/ehp.93100189
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicology of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans.

Abstract: Few environmental compounds have generated as much interest and controversy within the scientific community and in the lay public as polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs). Their ubiquitous presence in the environment and the risk of accidental exposure has raised concern over a possible threat of PCDDs or PCDFs to human health. The most extensively studied and potent isomer is 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD or dioxin). Dioxin is a multisite toxicant in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…P-450-dependent enzyme activities, mRNA, or protein. Vanden Heuvel et al (147,148) showed that TCDD-mediated increases in CYP1A1 mRNA were detectable following a single dose of 0.1 ng/kg, which produces a concentration of TCDD in the liver equivalent to a chronic dose of 2-5 pg/kg per day.…”
Section: Cypiai and Cypia2mentioning
confidence: 99%
“…P-450-dependent enzyme activities, mRNA, or protein. Vanden Heuvel et al (147,148) showed that TCDD-mediated increases in CYP1A1 mRNA were detectable following a single dose of 0.1 ng/kg, which produces a concentration of TCDD in the liver equivalent to a chronic dose of 2-5 pg/kg per day.…”
Section: Cypiai and Cypia2mentioning
confidence: 99%
“…(1). The 75 PCDD homologs show different toxicities depending on the degree of chlorination and on the position of the chlorine atoms in the dibenzo ring, the most toxic ones being the tetrachlorosubstituted (2,3). They are chemically stable and able to bioaccumulate in organisms and are thus extremely significant for the environment (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, if humans are not exposed to a chemical carcinogen, then the expectation that that chemical will be a carcinogenic hazard to humans must be recognized as not being readily possible. Yet, even this apparent comfort might be short-lived because other laboratory chemical curiosities or industrial intermediates have had or do exhibit widespread human exposure: examples are vinyl chloride (27)(28)(29)(30), methyl isocyanate (31), tetrachlorodibenzo-p-dioxin (32,33), and 1,3-butadiene (34,35). Further, the concept of "safe" exposure levels to carcinogens accepts the erroneous concept of threshold (36).…”
mentioning
confidence: 99%